Blockade of Rostral Ventrolateral Medulla Apelin Receptors Does Not Attenuate Arterial Pressure in SHR and L-NAME-Induced Hypertensive Rats - Griffiths, Philip R.; Lolait, Stephen J.; Pearce, Louise E.; McBryde, Fiona D.; Paton, Julian F. R.; O’Carroll, Anne-Marie (Frontiers in Physiology, 2018)
Dysfunction of the apelinergic system, comprised of the neuropeptide apelin mediating its effects via the G protein-coupled apelin receptor (APJ), may underlie the onset of cardiovascular disease such as hypertension. Apelin expression is increased in the rostral ventrolateral medulla (RVLM) in spontaneously hypertensive rats (SHRs) compared to Wistar-Kyoto (WKY) normotensive rats, however, evidence that the apelinergic system chronically influences mean arterial blood pressure (MABP) under pathophysiological conditions remains to be established. In this study we investigated, in conscious unrestrained rats, whether APJ contributes to MABP and sympathetic vasomotor tone in the progression of two models of hypertension – SHR and L-NAME-treated rats – and whether APJ contributes to the development of hypertension in pre-hypertensive SHR. In SHR we showed that APJ gene (aplnr) expression was elevated in the RVLM, and there was a greater MABP increase following microinjection of [Pyr1]apelin-13 to the RVLM of SHR compared to WKY rats. Bilateral microinjection of a lentiviral APJ-specific-shRNA construct into the RVLM of WKY, SHR, and L-NAME-treated rats, chronically implanted with radiotelemeters to measure MABP, decreased aplnr expression in the RVLM and abolished acute [Pyr1]apelin-13-induced increases in MABP. However, chronic knockdown of aplnr in the RVLM did not affect MABP in either SHR or L-NAME-treated rats. Moreover, knockdown of aplnr in the RVLM of prehypertensive SHR did not protect against the development of hypertension. These results show that endogenous apelin, acting via APJ, is not involved in the genesis or maintenance of hypertension in either animal model used in this study.